CPW-Fed Circular Microstrip Patch Antenna for Early Detection of Skin Cancer - Kumar Yadav, Navneet; Maurya, Ajay Kumar; Prakash, Ravi (Journal of Neonatal Surgery, 2025)
An antenna is a radiating object which converts the electrical energy to EM radiations. Oncology is branch which deals with the study of Tumor cells. This research paper proposes an antenna for early detection of Skin Cancer. The proposed antenna consists of CPW Fed, Microstrip patch antenna, which is of Flower shape with Crescent slots. The proposed antenna radiates at a frequency of 10 GHz with the return loss of 22.50dB and has a bandwidth of 3.28GHz resonating at 10GHz and at 4GHz with an impedance bandwidth of 3.37GHz. It has maximum gain of 9.42dB. The proposed antenna is designed on the Felt substrate, with the refractive index of 1.22. It also consists of an AMC backed structure to enhance the gain of the antenna. The proposal designed using HFSS (High frequency structure simulator). Rbin caliskan at all, Proposed a Microstrip Patch Antenna Design for Breast Cancer Detection. In this paper a 3D breast structure has different permittivity and conductivity is modelled in HFSS by using Finite Element Method (FEM) to solve electromagnetic field values and a microstrip patch antenna operating at 2.45 GHz is designed and substrate material is FR4 (Ir = 4.4 F/m). Slotting on microstrip patch and modifying ground plane, imaging quality is increased. About this, electric field, magnetic field distribution and current density on the antenna are evaluated.